PEMANFAATAN LIMBAH KULIT lKAN MENJADI KERUPUK (RAMBAK) - Kristianingrum, Susila; Arianingrum, Retno; Sulastri, Siti (Universitas Negeri Yogyakarta, 2006)
This program of implementation Science, Technology and Arts (Ipteks) intended to introduce and give skill training about making chips from fish skins (kerupuk kulit ikan) to the community in Tanjungsari Sub district, Gunungkidul Regency. In this area, there are plenty of fish skins that can pollute and disturb the beauty of the environment. Producing chips from fish skins can reduce the pollutant and increase the value of fish skins.The program was held by giving information and demonstration methods in two locations with different participants. The first program was held in Tanjungsari Sub-district Hall for 35 participants, who were village chiefs' wives. The second program was held at Baron beach hall to accommodate 20 participants, consisting of fishermen's wives and members of youth group.The questionnaire result of first program showed that 85.71 % of theparticipants considered this program profitable and 74.28% said that they were interested to develop business in producing fish skin chips. All the participants (100%) of the second program said that the program was profitable and they were interested to develop business in producing fish skin chips. Thus, the program succeeded in broadening the participants' perspectives and skills on how to make use of waste, turning it into fish skin chips and to motivate the participants to develop business using the knowledge and skills already obtained.Key words:fish skin waste.fish skin drips